Functional Implications of the Flat-Topped Talus Following Treatment of Idiopathic Clubfoot Deformity. Issue 4 (22nd October 2020) - Shivers, Claire; Siebert, Matthew; Zide, Jacob R.; Tulchin-Francis, Kirsten; Stevens, Wilshaw; Borchard, Justine; Riccio, Anthony; Zide, Jacob R.
Category: Hindfoot; Other Introduction/Purpose: The flat-top talar dome is a well-known potential consequence of both operative and non-operative clubfoot management. While it is assumed that patients with a flat-top talus will have greater problems with daily activity, the functional impact of this deformity has not been characterized in the literature. The purpose of this study is to analyze the relationship between talar dome morphology and ankle function at skeletal maturity in patients treated for idiopathic clubfoot deformity during infancy. Methods: 33 skeletally mature patients (average age 17.9 years, SD 1.6 years) with 52 idiopathic clubfeet were identified from our institution's clubfoot registry. Plain weight bearing lateral foot films, gait analysis and patient reported outcomes (PRO) using the Pediatric Orthopaedic Data Collection Instrument (PODCI) were obtained in all patients. Radius of curvature (ROC) of the talar dome and tibial plafond were measured along with numerous other parameters of talar and calcaneal morphology. Other measurements included talar dome radius to talar length (R/L) ratio, opening angle of the talar dome (alpha-angle), and talar dome to tibial plafond ROC (TD/TP) ratio. All measurements were correlated to PODCI scores and gait analysis data. Results: Patients demonstrated variability in talar dome ROC (mean 33.1mm, SD 19.6mm), R/L ratio (mean 0.60, SD 0.39), alpha- angle (mean 88.7°, SD 29.5°) and TD/TP ratio (mean 1.17, SD 0.44). Increased TD/TP ratio correlated negatively with maximal plantarflexion (r=0.404, p=0.005), ankle range of motion (ROM) (r=0.383, p=0.008) and maximum power generation during step off (r=0.381, p=0.008). Higher alpha-angle correlated positively with plantarflexion (r=0.404, p=0.005), ankle ROM (r=0.383, p=0.008) and maximum ankle power generation (r=0.381, p=0.008). Lower talar dome ROC correlated with increased maximum power generation (r=0.326, p=0.025). Increased R/L and TD/TP ratios correlated negatively with PODCI happiness domain scores (r=-0.353, p=0.044; r=-0.377, p=0.025, respectively). Talar length correlated with higher happiness and global function scores (r=0.393, p=0.024; r=0.360, p=0.040, respectively) and lower pain scores (r=0.354, p=0.043). Conclusion: While flatness of talar dome correlates significantly with altered gait mechanics, the effects on patient reported function are more modest during the second decade of life. Further study is required to assess the longer-term effects of the flat top talus on function and joint health.